2014
DOI: 10.1200/jco.2013.54.1086
|View full text |Cite
|
Sign up to set email alerts
|

Psychosexual Functioning Among Adult Female Survivors of Childhood Cancer: A Report From the Childhood Cancer Survivor Study

Abstract: A B S T R A C T PurposeChildhood cancer survivors may be at risk for impaired psychosexual functioning as a direct result of their cancer or its treatments, psychosocial difficulties, and/or diminished quality of life. Patients and MethodsTwo thousand one hundred seventy-eight female adult survivors of childhood cancer and 408 female siblings from the Childhood Cancer Survivor Study (CCSS) completed a self-report questionnaire about their psychosexual functioning and quality of life. On average, participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
98
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(107 citation statements)
references
References 23 publications
6
98
3
Order By: Relevance
“…2 Although more children and teens are surviving their cancer diagnoses and living into adulthood, recent data from the Childhood Cancer Survivor Study (CCSS) identifies gonadal failure as a long-term health concern. 3,4 Indeed, the CCSS reported that 6.3% of childhood survivors experience acute ovarian failure immediately after treatment, and 8% experience premature ovarian failure at some point after the end of treatment. 5,6 Preservation and restoration of fertility are key aspects for enhancing quality of life in this population, and studies have found that 60% of survivors desire to rear biological children and >65% of childhood or young adult cancer survivors have used or want information about infertility and options for having children.…”
mentioning
confidence: 99%
“…2 Although more children and teens are surviving their cancer diagnoses and living into adulthood, recent data from the Childhood Cancer Survivor Study (CCSS) identifies gonadal failure as a long-term health concern. 3,4 Indeed, the CCSS reported that 6.3% of childhood survivors experience acute ovarian failure immediately after treatment, and 8% experience premature ovarian failure at some point after the end of treatment. 5,6 Preservation and restoration of fertility are key aspects for enhancing quality of life in this population, and studies have found that 60% of survivors desire to rear biological children and >65% of childhood or young adult cancer survivors have used or want information about infertility and options for having children.…”
mentioning
confidence: 99%
“…Childhood Cancer Survivor Study found that adult female survivors of childhood cancer reported lower sexual functioning, lower sexual interest, lower sexual desire, lower sexual satisfaction and lower sexual activity compared with siblings [4]. By respect to Moroccan culture, we didn't have any question about sexuality.…”
Section: Discussionmentioning
confidence: 88%
“…The category with the lowest probability of marriage were patients with CNS tumors, cranial radiation, impaired processing efficiency, and short stature. There is no difference in divorce patterns between survivors and their peers [4].…”
mentioning
confidence: 86%
“…Radiation affecting ovarian and uterine functions has been linked to pregnancy complications including infertility, spontaneous abortion, acute ovarian failure, low birth weight and stillbirth. Also, sexual malfunction among female survivors of childhood cancers was partially related to cranial radiation treatment [21].…”
Section: Discussionmentioning
confidence: 99%